The Movement Peasants of Kurdistan: (1995 – 1998) - Zhelwan Abdullah Ahmed; Amanj Hasan Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The Kurdistan farmers Movement (1995-1998) was one of the organizations that was formed after the uprising in South Kurdistan, our research has determined the first conference, which describes how the movement was formed and its activities, its role in the Kurdistan Regional civil war and its relationship with the political parties, later on we discussed the end of the farmers Movement and later re-created and changed its name in 1998. The research consists of several topics, as follows: The first topic: we discussed the beginnings of the farmers movement and the efforts made by the farmers’ supervisory committee. The second topic: In this topic we have discussed the first conference of the movement and its activities. The third topic: the impact of the civil war on the movement and the attack on the movement. Fourth topic: In this topic we have briefly discussed the position of other parties towards the farmers movement and their position towards the movement. The fifth topic: a brief discussion of the problems and conflicts within the movement and the end of the movement's activities and efforts to revive the movement. At the end, we present the conclusions and documents we relied on in the study, followed by a list of sources we used, and some interviews.